The Role Of Epidemiological Surveillance And Clinical Infection Control Strategies In Healthcare Setting (The Review of Diabetic Studies, 2025)
Healthcare keeps changing, always caught between fighting outbreaks and tackling healthcare-associated infections (HAIs). In this review, epidemiological surveillance and infection prevention and control (IPC) strategies work together to take on these challenges. The COVID-19 pandemic really shook things up—it forced healthcare to move fast, switching from slow, traditional surveillance to high-speed, tech-powered systems that use big data and artificial intelligence. Thanks to these upgrades, we can spot outbreaks earlier, track them in real time, and even predict what’s coming next. But the pandemic didn’t make everything better. Sure, all that extra attention on hygiene cut down infections like Clostridioides difficile. Yet, hospitals faced new problems—more devices in use, not enough staff—which actually drove up other infections, like central line-associated bloodstream infections (CLABSIs) and ventilator-associated events (VAEs). This article digs into how IPC strategies have changed, starting with basics like hand hygiene and moving up to smart tech like electronic monitoring and automated room disinfection. I break down how well these tools work, what they cost, and the real-life headaches that come with putting them in place. Antimicrobial resistance (AMR) hangs over it all, only getting worse during the pandemic and making it clear we need connected approaches to surveillance and stewardship. In the end, keeping patients safe means mixing the sharp edge of AI analytics with the irreplaceable skills of healthcare workers, strong leadership, and a culture that puts safety first. If we want resilient, effective healthcare, we have to invest smartly, govern ethically, and work together across disciplines. That’s how we turn today’s innovations into tomorrow’s safer hospitals.